Mechanical Properties of Coarse Aggregate Electric Arc Furnace Slag in Cement Concrete - Huu-Bang Tran (Civil Engineering Journal, 2021)
The feasibility of using EAF slag aggregate, fly ash, and silica fume in pavement Electric Arc Furnace Slag Concrete (CEAFS) is the focus of this research. EAF slag aggregate is volume stable and suitable for use in concrete, according to the findings of the testing. EAF slag was utilized to replace natural coarse aggregates in the CEAFS mixes. CEAFS was created by blending 50% crushed stone with 50% EAF slag in coarse aggregates, with fly ash (FA) and silica fume (SF) partially replacing cement at content levels (i.e. FA: 0, 20, 30, and 40%; SF: 0, 5, and 10%). The soil compaction approach was used to evaluate the optimal moisture level for CEAFS mixes containing EAF slag aggregate fly ash and silica fume. A testing program was used to investigate the weight of CEAFS units and their mechanical qualities (compressive strength, flexural strength, and elastic modulus). As a result, the fresh and hardened unit weights in the CEAFS are comparable. Moreover, variations in the concentration of mineral additives FA and SF in adhesives, as well as the CEAFS mixed aggregate ratio, have an impact on compressive strength, flexural strength, and elastic modulus at all ages. However, combining EAF slag aggregate with (FA0% +SF10%; FA10% +SF0%; FA10% +SF10%; and FA20% +SF10%) the CEAFS mixtures have improved mechanical characteristics over time. According to this study, CEAFS pavements can be made with EAF slag aggregate fly ash and silica fume. In addition, a formula correlation was suggested to compute CEAFS (i.e. compressive strength with elastic modulus and compressive strength with flexural strength). Doi: 10.28991/cej-2021-03091755 Full Text: PDF